GAGASAN PERTANGGUNGJAWABAN ORANGTUA TERHADAP TINDAK PIDANA PELANGGARAN BERLALU-LINTAS YANG DILAKUKAN ANAK DI BAWAH UMUR - Nico Alpino Siregar; Emilda Firdaus; Dessy Artina (Jurnal Ilmu Hukum, 2019)
AbstractThe purpose of this writing is to find out the responsibility of parents for traffic violations committed by minors and to know the idea of traffic violations committed by minors. This type of research will examine the subject matter in accordance with environmental space and identify problems through a normative juridical approach. Based on the results of the analysis in this study, it can be concluded: The responsibility of parents for traffic violations committed by minors due to negligence resulting in traffic accidents carried out by children cannot be transferred to their parents for criminal liability. The idea of criminal acts of traffic violations committed by minors should be transferred to the parents of the child on the grounds that the person responsible for the violation of the child is the parent of the child who has been negligent with his decision to make a leeway on the highway while still underage. Parents are stated as an aid to criminal acts committed by their children and are also responsible for victims of criminal acts committed by their children. Besides that, children can also be categorized as victims in the sense of victims from their parents' negligence because as long as their status is still a child, they are still under control parent or guardian. Keywords: Parental Responsibility, Criminal Driving, Children. AbstrakTujuan penulisan ini adalah mengetahui pertanggungjawaban orangtua terhadap tindak pidana pelanggaran berlalu-lintas yang dilakukan anak di bawah umur dan gagasan terhadap tindak pidana pelanggaran berlalu-lintas yang dilakukan anak di bawah umur. Jenis penelitian ini akan mengkaji pokok permasalahan sesuai dengan ruang lingkungan dan diidentifikasi masalah melalui pendekatan yuridis normatif. Pertanggungjawaban orangtua terhadap tindak pidana pelanggaran berlalu-lintas yang dilakukan anak di bawah umur yang karena kelalaiannya mengakibatkan kecelakaan lalu lintas yang dilakukan oleh anak tidak bisa dialihkan pertanggungjawaban pidananya kepada orang tuanya. Gagasan terhadap tindak pidana pelanggaran berlalu-lintas yang dilakukan anak di bawah umur sebaiknya dialihkan kepada orangtua anak dengan alasan yaitu penanggung jawab akibat pelanggaran pada anak adalah orangtua si anak yang telah lalai dengan keputusannya memberikan kelonggaran berkendara di jalan raya padahal masih di bawah umur. Orangtua dinyatakan sebagai perbantuan terhadap tindak pidana yang dilakukan anaknya dan turut bertanggungjawab terhadap korban dari tindak pidana yang dilakukan oleh anaknya, disamping itu anak juga bisa dikategorikan sebagai korban dalam artian korban dari kelalaian orang tuanya karena selama statusnya masih menyandang sebagai anak maka ia masih dibawah penguasaan orangtua atau walinya. Kata Kunci: Pertanggungjawaban Orangtua, Pidana Berkendara, Anak.